Foreign Direct Investment: A Wave To The Growth Of Retail Sector In India - Dr. R. Lavanya kumari and Ms. Smriti Nagaria (International Journal of Advanced Science and Technology, 2020)
India is one among the developing country; Government of India has allowed Foreign Direct Investment (FDI) in retail of major brand of products in retail industry which suggests that foreign companies in specific categories can sell products through their own retail shop within the country. So Foreign Direct Investment (FDI) is promoted and rise within the retail sector which affect the growth of the economy where major players and more sectors have opened for foreign investment. The Indian retail sector is emerging together as one of the vital sectors within the economy. During 2015, the entire market size was estimated to be around US$600 billion, comparing with a CAGR of 7.45% since 2000. The retail industry is predicted to grow to US$1.3 trillion by 2020, as compared a CAGR of 9.7% between 2000 and 2020. Currently the Government of India (GoI) has allowed 100% FDI in online retail of products to incentivize the international retailers. The paper highlights the significance of FDI and the growth of the Retail sector in India.